Utilizing the water-land-food security nexus to review the underperformance of smallholder farmers in the Eastern Cape, South Africa - Tantoh, Henry Bikwibili; McKay, Tracey J. M. (Frontiers in Sustainable Food Systems, 2023)
Supporting agriculture is crucial if food security and poverty alleviation are to be assured. In that regard two crucial aspects - water and land are central to supporting smallholder farmers. This is especially true for the Eastern Cape Province of South Africa with its high rates of poverty and food insecurity. However, attention is seldom given to the fundamental factors of farm production. Access to land for food production in the Eastern Cape is problematic, as is the water situation. It is among the driest provinces in the country, enduring extended drought conditions with resultant water scarcity challenges. This is compounded by poor adaptation strategies deployed by smallholder farmers. This study investigated the relationship between water, land and food security with respect to smallholder farmers in the Eastern Cape. It found that while both food security and incomes could be improved for these smallholder farmers if they had more access to land and water, these two factors alone are insufficient. These farmers also need access to agricultural extension services, markets, cost-effective transport and capital. Although the commercialization of these farmers is a way to improve rural livelihoods, the prevailing conditions in the province significantly inhibit this.